ANALISIS KEARIFAN LOKAL BUDAYA BAKAR TONGKANG BAGI MASYARAKAT BAGANSIAPI API KABUPATEN ROKAN HILIR - Zainudin, Mhd; Zaswita, Hermi (TSAQIFA NUSANTARA: Jurnal Pembelajaran dan Isu-Isu Sosial, 2024)
Riau is a province that has a variety of cultures, and one of them is the barge burning tradition in the city of Bagansiapiapi, Bangko District, Rokan Hilir Regency. This tradition has been passed down from generation to generation by ethnic Chinese in the city of Bagansiapiapi, so this makes this tradition held every year. Data collection was carried out using the library research method. The results of this research are that the barge burning culture is part of gratitude and respect for the king's ancestors from Chinese beliefs and as a reference in obtaining good fortune for the Chinese community in Bagansiapiapi, Rokan Hilir Regency, Riau.